Wheelbase Motor Project: An illustrative case study examining the determinants social enterprises within the United Kingdom could use to identify appropriate legal forms - Eakins, Keating (2009)
The social enterprises sector is one of the fastest growing sectors of the economy in the United Kingdom (UK), yet it is one of the least researched areas of the UK economy. The majority of research is focused on developing a theory of social enterprise and very few researchers have focused on the role of the legal forms in social enterprise operations. Selecting a legal form that replicates the organisation’s mission and objectives, rather than imposing a structure on the organisation, is one of the earliest hurtles social entrepreneurs face when developing a social enterprise. The purpose of this paper is to gain a greater understanding of the implications of legal forms in social enterprise research and practice by identifying determinants social enterprises within the UK could use to select an appropriate legal form. The paper will present the development and application of the Legal Forms Landscape, which maps the social enterprise legal form requirements of the UK, and Legal Forms Decisions Steps, which assists social entrepreneurs in identifying an appropriate legal form for their organisation, through an illustrative case study of Wheelbase Motor Project. The paper will conclude with a discussion of the study’s findings and the implications of legal forms in social enterprise research and practice.